Application of Clustering Method in Arabic Learning to Improve Speaking Skills for High School Levels - Abidah, Sa’idatul; Febriani, Suci Ramadhanti (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
The main goal of foreign language learning is to make students skilled in using the language both orally and in writing, as well as learning Arabic. However, there are many factors that cause students difficulties in the learning process. One of the contributing factors is the existence of various student characters in the classroom which makes teachers have to be smart in choosing learning methods. One of the appropriate strategies as an effort to overcome these problems is to use the "Clustering Learning Method". This research uses a qualitative approach, with a case study method; data is collected through observation and documentation. Data analysis in this study uses the theory of "Miles and Huberman". The results showed that the application of the clustering method could improve speaking skills in learning Arabic for class XI students of SMAN 10 Malang City. The improvement in question, namely the improvement of the process and student learning outcomes. This increase was seen in the learning process of the first and second meetings. Based on the results of the study, the researcher suggested to teachers that learning Arabic to improve speaking skills through the clustering method could be used as an alternative for teachers to teach other materials.